Can we predict which patients with plantar heel pain are more likely to benefit from insoles? A secondary exploratory analysis of a randomized controlled trial - N. Rasenberg; L. J. M. Dijkgraaf; P. J. Bindels; S. M. Bierma‐Zeinstra; M. vanMiddelkoop (Journal of Foot and Ankle Research, 2022)
Abstract Background Plantar heel pain (PHP) is a common cause of foot complaints, for which treatment with custom‐made insoles is frequently applied. So far few studies have investigated patient characteristics that predict response to these treatments. The aim of this secondary exploratory analysis was twofold; firstly, to identify patient characteristics that predict prognosis in patients with PHP treated with insoles, and secondly to identify characteristics that might interact with treatment with insoles. Methods Data from a randomized trial in which participants received either custom insoles (N = 70) or sham insoles (N = 69) were used. At baseline, information was collected on demographics, foot symptoms, foot and ankle range of motion, navicular drop, presence of neuropathic pain, physical activity and other illnesses in the last 12 months. The primary outcome of this study was the Foot Function Index score (FFI) at 26 weeks. Multivariable linear regression models were generated to identify patients characteristics that predict the outcome for each type of intervention (i.e. insoles and GP‐led usual care). Results We found two variables associated with a better function score at 26 weeks in patients treated with insoles, female sex (β − 9.59 95%CI ‐17.87; − 1.31) and a lower FFI score at baseline (β 0.56 95%CI 0.30; 0.82). Explorative analyses in patients treated with insoles showed no significant interaction effects between the type of insole (custom‐made versus sham) and any of the potential predictive factors. Conclusion When communicating about the effect of insoles for PHP clinicians should take sex and the amount of pain and disability at first presentation into account. Women and people with better foot function scores at baseline (according to FFI) might respond better to treatment with insoles in terms of foot function. Trial registration Trial registration: NTR5346.